The Influence of Fault Current & Soil Resistivity on the Substation Grounding Grid Behaviour - Permal N.; Osman M.; Ariffin A.M.; Ab Kadir M.Z.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer software; Electric fault currents; Soils; Current resistivity; Ground potential rise; Grounding grids; Resistance; Resistance increase; Soil resistivity; Step and touch voltage; Substation grounding; Top layers; Two-layer soil; Electric grounding